สิทธิมนุษยชนในอิสลามกับการรับรองสิทธิเสรีภาพตามรัฐธรรมนูญแห่งราชอาณาจักรไทย - สุดปรารถนา นีละไพจิตร (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Human rights are regarded as the fundamental right of humanity which not only certified by The Constitutions of Kingdom of Thailand but also said in the principles of Islam. And , primitive assumption predicted that the Islamic regulations have paid attention on the human rights guarantee which is corresponding with law of the Constitutions. This thesis found that Islam is one of religions provided the principles involved human rights. Moreover, a community of global Muslim countries united in and established The Organization of Islam Conference and prescribed The Cairo Declaration on Human Rights in Islam 1990. The human rights enacted in the Declaration were in line with The Universal Human Rights 1948 although some details were different. For the human rights attestation of Thai Muslims is predicted that although human rights in Islamic principles would similar with rights and freedoms that verified by The Constitutions but still need to ordain subordinate legislations in order that all of aspects in rights and freedoms will get successful results in the Islam rules. By the way, Thailand right now have provided 4 special laws that seriously protected to gave rights and freedoms in every day life and religious practicing for Muslims. This research found that human rights in Islam correspond with human rights in western world can be used in Thai society due to being plural culture society, especially in the southern province of Thailand. Moreover, it can be used Shari’a (Islamic law) to dissolve the conflict as an alternative justice system because if understand in the religious principles and concepts it could get along with Thai society.